Possible Link between History of Hypersensitivity to a Specific Non-steroidal Anti-inflammatory Drug (NSAID) and Positive Results Following Challenge Test to Alternative NSAIDs - Trombetta, Domenico; Imbesi, Selene; Vita, Giuseppe; Isola, Stefania; Minciullo, Paola Lucia; Saija, Antonella; Gangemi, Sebastiano (Arzneimittelforschung, 2009)
In subjects with hypersensitivity reactions to non-steroidal anti-inflammatory drugs (NSAIDs), the choice of suitable alternative drugs with the lowest risk of reaction is imperative for therapeutic management. A safe method to exclude drug hypersensitivity is to perform a challenge test for an alternative drug.The present study was conducted to:This retrospective study includes 524 patients with a history of hypersensitivity to NSAIDs admitted to undergo challenge test to an alternative anti-inflammatory drug. Statistical significance was achieved when odds ratio (OR) and risk ratio (RR) values were >1.8.39% of patients with hypersensitivity reactions to NSAIDs showed a positive challenge test for the alternative drug. Challenge tests for nonselective COX-2 inhibitors were positive in 16.2% of patients with previous reaction to a same drug class and in 12.9% of patients with a history of reaction to selective COX-2 inhibitors. No positive challenge test to a non-selective COX-2 inhibitor was found in patients with a history of hypersensitivity to nimesulide (CAS 51803-78-2). Challenge tests for selective COX-2 inhibitors were positive in 4.6% of patients with a previous reaction to nonselective COX-2 inhibitors and in 7.2% of patients with a history of reaction to selective COX-2 inhibitors. The RR of a positive challenge test to a non-selective COX-2 inhibitor was significant in patients who had a history of reaction to an analogous compound (P 0.21, OR 1.31, RR 1.26).In this study, selective COX-2 inhibitors represented the class of NSAIDs less frequently reported as responsible of adverse reaction. These data underline that there is a higher risk to find a positive challenge test to a non-selective COX-2 inhibitor than to a selective one in patients with previous adverse reactions to a non-selective COX-2 inhibitor. Moreover, the data evidence that females could have a higher risk compared to males to develop an adverse reaction to selective COX-2 inhibitors.In conclusion, it appears necessary to pay attention to the kind of NSAIDs reported as the cause of hypersensitivity in anamnesis, because it must be considered a successful guide in choosing the alternative drug to administer to the patient during the challenge test.
Keywords: Challenge test; COX-2 inhibitor; Hypersensitivity; Non-steroidal antiinflammatory drugs